Studi Kerusakan Jalan dan Cara Penanggulangannya pada Jalan Metro Tanjung Bunga, Kota Makassar - Lambang Basri Said; Musyafir Turu; Andi Alifuddin (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2023)
Roads are infrastructure that really supports people's living needs. In a broader dimension, the road network has a very important role in regional development, both national, regional and district/city areas according to the function of the road network. The condition of the road damage that occurred on a number of roads in the Makassar city area is increasingly worrying. The reason is that the condition of the road, which was initially slightly damaged due to being abandoned, is now getting worse with deep potholes. As a result, the smoothness of traffic and the safety and comfort of road users are disrupted. This research is intended to provide information regarding the types of road damage that occur, factors causing road damage and mitigation efforts carried out on the Tanjung Bunga metro road, Makassar city. The data collection method is in the form of a visual survey of types of road damage carried out directly in the field and data analysis using the Bina Marga method. The results of research in the field show that the greatest road damage on rigid pavement is grain release with a percentage of 0.076 percent on the left section and 0.089 percent on the right section, while the smallest type of road damage is corner cracking with a percentage of 0.0035 percent on the left section. and 0.0027 percent on the right side. The biggest type of road damage on flexible pavement is grain shedding with a percentage of 0.121 percent on the left section and 0.088 percent on the right section, while the smallest type of damage on the left section is edge cracking with a percentage of 0.003 percent and the type of damage sinking on the right section with a percentage 0.002 percent. Among the most dominant types of damage is grain release.